Mejoramiento poblacional del arroz en Cuba: situación actual y perspectivas - Pérez Polanco, R.; Châtel, M.; Guimarães, Elcio Perpétuo (Empresa Brasileira de Pesquisa Agropecuária, 2000)
We studied and characterized populations PCT-4 and PCT-7 and gene pool GPIRAT-10 at the Instituto de Investigación del Arroz at rice experiment station, situated south of Jíbaro in the Province of Sancti Spíritus, Cuba, between the 1996 wet season and the 1999 dry season. We aimed not only to characterize the germplasm but also to develop a population improvement strategy to increase blast (Pyricularia grisea Sacc.) resistance and to derive fixed lines. Of the three introduced germplasm materials, 400 lines were derived. Of these, 13 homozygous lines are being evaluated in observational yield trials across the country. GPIRAT-10 and PCT-4 were crossed with Cuban commercial varieties to produce local populations called PIACuba-1 and PIACuba-2, respectively. A plan was drawn up to use population improvement by recurrent selection to develop blast-resistant germplasm.